Agreement Among Stroke Faculty and Fellows in Treating Ischemic Stroke Patients With Tissue-Type Plasminogen Activator and Thrombectomy. Issue 1 (January 2017) - Ramadan, Ahmad-Riad; Denny, Mary Carter; Vahidy, Farhaan; Yamal, Jose-Miguel; Wu, Tzu-Ching; Sarraj, Amrou; Savitz, Sean; Grotta, James
Abstract : Background and Purpose—: The aim of this study is to determine agreement among vascular neurology fellows and faculty in treating patients with acute ischemic stroke with intravenous tissue-type plasminogen activator and intra-arterial thrombectomy (IAT). Methods—: Patients were evaluated simultaneously by at least 2 vascular neurology. Agreement was determined using kappa (κ) and intraclass correlation coefficients. Results—: In 60 patients, agreement was substantial for tissue-type plasminogen activator (κ=0.75 [95% confidence interval, 0.57–0.92]) and IAT (κ=0.63 [95% confidence interval, 0.30–0.96]), with no difference between fellow–fellow versus fellow–faculty. Intraclass correlation coefficient for National Institutes of Health Stroke Scale was 0.94 (95% confidence interval, 0.90–0.97) and κ for Alberta Stroke Program Early CT Score was 0.53 (95% confidence interval, 0.20–0.78). Rapidly improving or mild deficits caused disagreement for both tissue-type plasminogen activator and IAT, whereas interpretation of computed tomographic perfusion led to disagreement for IAT. Conclusions—: We found substantial agreement between vascular neurology fellows and faculty in treating with tissue-type plasminogen activator or IAT. Areas for improvement include recognition of stroke mimics, consensus on treating less severe strokes, and use/interpretation of imaging. Abstract : Supplemental Digital Content is available in the text.